PENGUKURAN LAJU PAPARAN RADIASI PADA RUANG PEMERIKSAAN MSCT 64 SLICE - Elisa Fitriani; Gatot Murti Wibowo (JRI (Jurnal Radiografer Indonesia), 2018)
Background:Radiation exposure rate measurements have been done on the MSCT 64 Slices examination room radiology section Dr. Moewardi Surakarta Hospital due to lack of repeat measurement after replacement of examination door. This study aims to determine the rate of radiation exposure and radiation safety in the examination room for workers and public refers to the NCRP report no. 147 about stuctural shielding design for medical x-ray imaging facilities. Methods: This type of research is quantitative research with survey approach. This research was conducted in March 2018. Data collection was done by observation, documentation, and measure the radiation exposure in measurement points some places, which are controlled and uncontrolled areas. Data analysis was done descriptively by comparing data with NCRP report no.147. Results:The measurement results of the rate of radiation exposure, point A and B shows the leakage of radiation exposure. While the point of C, D, E no leakage of radiation. Conclusions: The value of background radiation exposure in the MSCT 64 Slices examination room radiology section Dr. Moewardi Surakarta Hospital exceeds the dose rate base on the height of the location according to UNSCEAR. Leakage of radiation exposure occuring at point A is woorkes door and point B front door MSCT 64 Slices examination room not safe for workes and public because it exceeds the limit of radiation exposure rate value which allowed